Liquid-Crystalline Suspensions of Photosensitive Paramagnetic CeF3 Nanodiscs - Chaput, Frédéric (Langmuir : the ACS journal of surfaces and colloids, 2019)
The design of high-performance energy-converting materials is an essential step for the development of sensors, but the production of the bulk materials currently used remains costly and difficult. Therefore, a different approach based on the self-assembly of nanoparticles has been explored. We report on the preparation by solvothermal synthesis of highly crystalline CeF3 nanodiscs. Their surface modification by bisphosphonate ligands led to stable, highly concentrated, colloidal suspensions in water. Despite the low aspect ratio of the nanodiscs (∼6), a liquid-crystalline nematic phase spontaneously appeared in these colloidal suspensions. Thanks to the paramagnetic character of the nanodiscs, the nematic phase was easily aligned by a weak (0.5 T) magnetic field, which provides a simple and convenient way of orienting all of the nanodiscs in suspension in the same direction. Moreover, the more dilute, isotropic, suspensions displayed strong (electric and magnetic) field-induced orientation of the nanodiscs (Kerr and Cotton-Mouton effects), with fast enough response times to make them suitable for use in electro-optic devices. Furthermore, an emission study showed a direct relation between the luminescence intensity and magnetic-field-induced orientation of the colloids. Finally, with their fast radiative recombination decay rates, the nanodiscs show luminescence properties that compare quite favorably with those of bulk CeF3. Therefore, these CeF3 nanodiscs are very promising building blocks for the development and processing of photosensitive materials for sensor applications